Desconsideração da personalidade jurídica na recuperação judicial - Koury, Felipe Frota de Almeida (2020)
Judicial reorganization in Brazil was instituted by Law 11.101/2005 and it is main objective is to preserve economic activity, as long as it is possible for the debtor society to overcome the crisis. In spite of the innovation brought by the judicial reorganization institute to the national legal system, the referred Law ceased to regulate and was omitted in several common points in commercial relations. One of these omissions was the possibility or not of disregard of the corporate entity in insolvency and, specifically, in judicial reorganization. However, Law 11.101/2005 encompassed bankruptcy acts, which are the chances of committing fraud during the recovery process. We must also bear in mind the study of substantive consolidation in the event of fraud and equity confusion in the recovery process. Although there is a legal provision for bankruptcy acts and broad jurisprudential application of substantive consolidation, there is jurisprudence in the São Paulo Court of Justice determining the opening of the legal personality disregard incident to hold partners who committed an act of fraud in the process responsible recovery, without considering the legal provision for bankruptcy acts and substantive consolidation. The Court's attempt to avoid committing a fraudulent act, determining the establishment of the incident of disregard of the corporate entity, however, does not observe the principles of Law 11.101/2005, nor does it analyze the characteristics of the institute and the compatibility of the effects of the application of the disregard of the corporate entity in the judicial recovery